Current knowledge on correlations between highly prevalent dental conditions and chronic diseases: an umbrella review [dataset] - Seitz, Max; Listl, Stefan; Bartols, Andreas; Schubert, Ingrid; Blaschke, Katja; Haux, Christian; Zande, Marieke M. van der (Universität, 2019)
Introduction: There are existing studies investigating relationships between chronic systemic and dental conditions, but it remains unclear how suc...